Potential heterosis aáociated with developmental and metabolic proceáes in sorghum and maize - Eastin, J.D.=700 1 Petersen, C.L.; Zavala-García, F.; Dhopte, A.; Verma, P.; Ongulea, V.B.; Witt, M.W.; González Hernández, V.; Livera Muñoz, M.; Gerik, T.J.; Gandoul, G.I.; Hovney, M.R.A.; Mendoza Onofre, L.
Sumario (En)
Ilus.; 28 ref.
Keywords: ZEA MAYS; SORGHUM BICOLOR; VIGOR HIBRIDO; METODOS DE MEJORAMIENTO GENETICO; SEMILLAS